Analisis Pengendalian Kualitas Produksi Kaleng PT XYZ dengan Menggunakan Metode RCA (Root Cause Analysis) - Michael A. Irawan; Farida Pulansari (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
PT XYZ was established as a company engaged in packaging manufacturing, especially biscuit cans and paint cans. PT XYZ was established in 1977 and has grown to become one of the leading manufacturing companies in Indonesia. In the production process, there are often many rejected goods which causes a lot of waste to occur and a decrease in profits due to the large number of rejected products at PT XYZ. Therefore, it is necessary to carry out quality control to find out the meeting point that causes problems to occur every period. In the quality control process using RCA (Root Cause Analysis). From the results of quality control, it was found that the dominant cause of the large number of rejected goods that occurred, namely the type of rupture reject which had a percentage of 98%, so that there was a need for improvement in the production process of the PT XYZ company that occurred which caused the product to reject.